Antimicrobial prescribing quality for sexually transmitted infections: a scoping review - Harlan Smith; Josephine Wen; Zohal Rashidzada; Jenna Maleki; Xin Fang; Karin Thursky; Rodney James; Courtney Ierano (Sexual Health, 2026)
Sexually transmitted infections (STIs) place a substantial burden on outpatient health care and are a key focus for antimicrobial stewardship due to rising antimicrobial resistance. Suboptimal treatment can result in ongoing transmission, reinfection and complications, such as pelvic inflammatory disease. Evaluating prescribing quality is essential to improve patient care and support stewardship efforts. This review synthesises evidence on antimicrobial prescribing quality for STIs and identifies gaps to inform targeted interventions for this unique but critical setting. This PRISMA-ScR scoping review searched Ovid MEDLINE and Embase for English-language studies published from 2015 to May 2025 assessing antimicrobial prescribing quality for STIs in outpatient settings. Results were summarised descriptively; no formal critical appraisal was undertaken. Fifteen studies assessing antimicrobial prescribing quality for STIs in outpatient settings were included, predominantly from high-income countries, and focused on Neisseria gonorrhoeae and Chlamydia trachomatis. Substantial heterogeneity was observed in analytic units, denominators and outcome definitions, limiting comparability across studies. Prescribing quality was primarily assessed against national guidelines, although approaches varied from antimicrobial choice alone to multi-criteria and all-or-nothing assessments, with inconsistent terminology used throughout. Reported guideline concordance varied widely, with generally higher concordance for chlamydia than gonorrhoea. Antimicrobial prescribing for STIs in outpatient settings is both understudied and highly variable. Despite increasing global policy emphasis on antimicrobial stewardship, there are no standardised frameworks to support routine auditing in this setting. Developing standardised auditing approaches would improve surveillance, support stewardship efforts and identify opportunities to optimise prescribing practices across a broader range of STIs.